Serum levels of tissue factor pathway inhibitor: Potential association with Raynaud's phenomenon and telangiectasia in patients with systemic sclerosis. Issue 8 (13th April 2021) - Norimatsu, Yuta; Miyagawa, Takuya; Fukui, Yuki; Omatsu, Jun; Toyama, Satoshi; Awaji, Kentaro; Ikawa, Tetsuya; Watanabe, Yusuke; Yoshizaki, Ayumi; Sato, Shinichi; Asano, Yoshihide
Abstract: Vasculopathy is a critical step of systemic sclerosis (SSc) development, bridging between autoimmune inflammation and tissue fibrosis. Impaired coagulation system is a part of SSc vasculopathy, but the role of tissue factor pathway inhibitor (TFPI), a critical regulator of the extrinsic coagulation pathway, remained unknown. Therefore, we evaluated the clinical correlation of serum TFPI levels in SSc patients. Serum TFPI levels were comparable between SSc and control participants, but SSc patients with Raynaud's phenomenon and telangiectasia had significantly lower serum TFPI levels than those without. Importantly, there was a significant positive correlation between serum TFPI levels and protein S activity. These results support the critical role of impaired coagulation system in SSc.